Can we predict short-term side effects of methylphenidate immediate-release? - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2008)
Objective. In children and adolescents who were prescribed immediate-release methylphenidate (MPH-IR) for the first time, we aimed to investigate the effect of gender, psychiatric co-morbidity and the baseline severity of clinical symptoms on the short-term side-effects of the medication. Method. In a clinical sample, over a period of 6 months, all MPH-naive patients with attention deficit hyperactivity disorder (ADHD) (N = 90; male, n = 73; female, n = 17) age: 9.0 +/- 2.2 years (5-16 years)) were included. Patients were prescribed MPH-IR 10-30 mg/day (17.6 +/- 4.95). The assessment included structured measurements, including the Turgay Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV)-Based Child and Adolescent Behavior Disorders Screening and Rating Scale (T-DSM-IV-S) (parents and teachers), Conners' Teacher Rating Scale for ADHD-Short version (teachers). Parents also completed the Barkley Stimulants' Side Effects Rating Scale (BSSERS) at baseline and on the third, seventh and 15th days of medication. Results. Repeated measures multiple ANOVA revealed an overall significant difference in BSSERS between the baseline measures and the 15th day (P < 0.01). On the 15th day, only the loss of appetite item severity scores increased (P=0.001), whereas the scores of irritability, proneness to cry, anxiety, nail biting and euphoria items decreased significantly. In post hoc analyses, when subjects whose side effects increased and did not increase were compared, chi-square tests revealed a significant difference (P=0.029) only for the presence of co-morbidity, and no difference for the gender, age, dosage of MPH, and the baseline severity of inattentiveness and/or hyperactivity. Discussion. The only significant increase during MPH treatment was for the loss of appetite item on BSSERS. Our results suggest that some of the BSSERS items may represent both the ADHD symptoms and the side effects. When overall BSSERS item severity is considered, having a co-morbid diagnosis may be predictive of more severe adverse effects.
Keywords: methylphenidate; immediate-release; side-effects; adverse effects; ATTENTION-DEFICIT/HYPERACTIVITY DISORDER; DEFICIT-HYPERACTIVITY DISORDER; CHILDREN; ADOLESCENTS; HEIGHT; SLEEP; BOYS